Determinants of Health - Taxonomic Analysis of Health of Elder Subpopulation in European Countries - Wierzbicka, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The intensive in recent times interest about the relationship between health and life style is the response to the rapid pace of population aging. Countries tend to be societies of health, presenting health problem as the main subject of many debates, both social and political. This situation requires various analysis, relevant to the implementation of appropriate, effective strategies, as well as education and promotion of health. The purpose of this paper is to analyze and compare health status of elder subpopulation in selected European countries. The study was conducted on the basis of the fundamental determinants of health related to lifestyle from the EUROSTAT database. The use of Hellwig's taxonomic measure of development will allow for the appropriate arrangement and indication of the countries that have the highest level of health status of people in three age intervals: 65-74, 75-84, 85 and more. In the first two age groups, apart from Poland, the study will include Bulgaria, Cyprus, Czech Republic, Spain, Hungary, Latvia, Malta and Slovenia. EUROSTAT does not have complete data on the eldest people, that is why the study in this part of the work is limited only to five countries. The results will help to determine health status of elder people in Europe, and also to create a comparative ranking of countries according to the level of the studied phenomenon.